A permanêcia dos jovens na agricultura familiar, nas comunidades rurais de Umarí e projeto assentamento Bom Lugar I, Upanema/ RN - Oliveira, Suzana Medeiros de Carvalho (Universidade Federal Rural do Semi-Árido, 2019)
This study analyzed the permanence in the field of young people, Projeto de Assentamento Bom Lugar I Settlement Project and in the community of Umari, located in the municipality of Upanema / RN. The objective of this work was to understand how young people stay in the countryside, besides their importance in family farming activities, and to know their motivations for remaining in rural areas. The choice of this topic was made through a Course in Field Development Project that I studied in the Field Education Licentiate course (LEDOC) and because I already had an interest in studying rural communities, family farming. The methodological paths were through semi-structured interviews of a qualitative nature, and through the dynamics of "snowball" with the purpose of maintaining rapprochement with the young people of the referred communities. Interviews were conducted with seven young women, two women and five men. The dialogue with the youth of the communities made it possible to verify that their permanence in rural areas occurs through their activities in family agriculture. These activities are necessary to develop your life projects. The experience of young people comes from a generation and is guided by the family tradition that is to remain in the rural environment. It prevails as the powerful attraction that youngsters when they see that they want to stay with their parents' routines. Respondents prefer to continue with the activities in the field and want to preserve what is already built on the properties to work with. Minimal conditions such as access to contextualized education, the reality of the countryside, access to the health system and infrastructure in rural communities are necessary so that young people can stay in the countryside, without needing to seek better conditions elsewhere. In this case, not only the cultural aspects of the families are responsible for the permanence of the young people in the field, but the lack of opportunities to work in other areas of work, which is what keeps them in the field, their stay in the field, and in other cases they must leave for lack of employment, and have not had opportunity to study. This study brought some reflections on the importance of family Projeto de Assentamento Bom Lugar I and in the community of Umari, Upanema, RN. In this sense, it is important public policies that value and opportunities for young people to stay in the field and contribute to the development of family farming and better living conditions for their families.
Monografia
Keywords: Comunidades rurais; Jovens; Agricultura familiar; Rural communities; Young people; Family farming; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL